ANALISIS TAX GAP ANTARA REALISASI PENERIMAAN PAJAK DENGAN POTENSI PAJAK DARI BELANJA APBD: STUDI KASUS PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2010 - , Ambar Arum Ari Mulyo; , Dr. Poppy Ismalina, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Along with the decrease of natural resource export toward the state revenue, the role of tax as one source of revenue for the country becomes very important. However, the increase of tax revenue does not exactly reflect the actual performance of tax. One of tax performance measurement which is accurate is tax gap that is the difference between the potential of revenue and its realization. Income tax article 21, is one of sources of local expense financing, of which 20% from the income tax in article 21 will be distributed to local government in the form of proportionality fund. Directorate General of Taxes in 2011 had calculated tax gap over APBD in KPP Pratama Yogyakarta as to Rp185.7 billion. It shows that there are many potentials of revenue that have not been realized by KPP Pratama Yogyakarta. This research aims at finding out the estimation of the number of income tax gap based on article 21 over APBD of DIY Provincial Government in 2010, finding out the factors causing tax gap, analyzing the alternative solution to reduce tax gap, and analyzing an alternative appropriate mechanism over the tax cutting, payment, and reporting by expenditure treasurer. This research uses quantitative approach by calculating the number of tax gap and one-way Anova analysis, as well as qualitative approach by analyzing of in depth-interview result. The population of this research is 29 SKPD, which is 11 SKPD were taken as sample with purposive sampling method that was divided into three stratification, those are big, medium, and small. Based on the research, it is found that the number of income tax gap in article 21 is Rp1,829,996,188. From the result of one-way Anova analysis, it is found the difference of average tax gap among three strata. Factors causing income tax gap as in article 21 is the expenditure treasurer has lack of compliance level, the method of calculating tax potential which does not described the actual tax gap, the complex procedures of filling the SPT form, lack of supervisory and testing toward the compliance level of the treasurer, and the socialization method which is less effective. The efforts conducted to reduce the tax gap of income tax as in article 21 are by revising the regulation, standard calculating method of tax potential, revising the socialization method and developing the service quality, also by improving supervisory function, regulation, calculating mechanism, the tax payment, and tax reporting which are conducted by simplifying the tax subject limit, tax object, tax application base, SPT periodic PPh article 21 reporting form, as well as applications which can bridge the application of KPPN/DPPKA with the application of income tax article 21.